Ambulance and aeromedical accident rates during emergency retrieval in Great Britain. Issue 5 (23rd April 2008) - Lutman, D; Montgomery, M; Ramnarayan, P; Petros, A
Abstract : The retrieval of critically ill patients is frequently done in difficult circumstances and often under considerable time pressures. These adverse conditions have a finite risk of serious injury or death. The level of risk is poorly described in the literature and reliable data on accident rates are hard to find. Most of the information comes from North America. There are no clear published statistics for the UK. We report for the first time data on accidents and casualties involving vehicles classified as having an ambulance body type and air ambulances within Great Britain between 1999 and 2004.